Pengaruh Beban Kerja, Konflik Kerja dan Dukungan Sosial terhadap Kesejahteraan Psikologis Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Asahan - Adinda Putri Mayang Sari; Abdul Rahman (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the influence of workload, work conflict, and social support on employees’ psychological well-being at the Department of Population and Civil Registration of Asahan Regency. The main problem addressed in this research is the increasing work demands and service pressure faced by public sector employees, which may affect their psychological conditions and overall well-being. The objective of this study is to analyze the partial and simultaneous effects of workload, work conflict, and social support on psychological well-being. A quantitative approach was employed using a descriptive-explanatory design. The population consisted of 70 employees, which were all used as the sample through a saturated sampling technique. Data were collected using questionnaires and analyzed using multiple linear regression with SPSS version 25, including classical assumption tests and hypothesis testing. The results show that workload, work conflict, and social support significantly influence employees’ psychological well-being both partially and simultaneously. Social support emerges as the most dominant factor in improving psychological well-being. These findings indicate that a supportive work environment, balanced workload, and well-managed workplace conflict play an important role in enhancing employees’ psychological conditions. The study suggests that improving organizational support systems can strengthen employee well-being in public service institutions.